2021
DOI: 10.3390/wevj12040253
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Matching Method of a Battery-Supercapacitor Hybrid Energy Storage System for Electric Vehicles

Abstract: To satisfy the high-rate power demand fluctuations in the complicated driving cycle, electric vehicle (EV) energy storage systems should have both high power density and high energy density. In order to obtain better energy and power performances, a combination of battery and supercapacitor are utilized in this work to form a semi-active hybrid energy storage system (HESS). A parameter matching method of battery-supercapacitor HESS for electric vehicles (EVs) is proposed. This method can meet the performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To reduce the complexity of the power model, the efficiency of the hybrid vehicle transmission, the DC/AC converter, and the motor are all set to constants. The main characteristic parameters of the EV in this study are listed in Table 1, 31 and the required power of the vehicle can be obtained by Equation ( 1)…”
Section: Required Power Model Of the Vehiclementioning
confidence: 99%
See 3 more Smart Citations
“…To reduce the complexity of the power model, the efficiency of the hybrid vehicle transmission, the DC/AC converter, and the motor are all set to constants. The main characteristic parameters of the EV in this study are listed in Table 1, 31 and the required power of the vehicle can be obtained by Equation ( 1)…”
Section: Required Power Model Of the Vehiclementioning
confidence: 99%
“…The detailed parameter matching method has been summarized in our previous study, and the results are shown in Table 4. 31 The battery pack is configured with 100 cells in series, and its parallel number is 25. The series-parallel connection number of the ultracapacitor pack is 135 and 3, respectively.…”
Section: Parameter Matching Of the Battery Pack And Ultracapacitor Packmentioning
confidence: 99%
See 2 more Smart Citations
“…The parallel number of ultracapacitor pack is 3 and the series number is 135. 33 In order to fully utilize the high short-time discharge rate of the ultracapacitor, the voltage of the ultracapacitor cell and pack should be maintained in the range of [1.35, 2.7] V and [182. 25,499.5] V. The core parameters of battery and ultracapacitor are summarized in Table 3.…”
Section: Modeling Of Battery and Ultracapacitor Packmentioning
confidence: 99%